High-entropy ceramic strengthened coating based on induction heating, ultrasonic oscillation and pulse current assisted laser cladding and preparation method thereof
By employing induction heating, ultrasonic oscillation, and pulsed current-assisted laser cladding technology, a high-density, high-strength multi-component composite coating was prepared, solving the problems of uneven coating performance and insufficient bonding strength in traditional laser cladding technology, and realizing the preparation and application of high-performance coatings.
Patent Information
- Application Number
- CN202511163655.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-20
- Publication Date
- 2025-11-04
AI Technical Summary
Traditional laser cladding technology suffers from problems such as uneven temperature field distribution in the molten pool, concentrated thermal stress, micropores, unsatisfactory bonding strength at the substrate-coating interface, and poor coating performance consistency during coating preparation, making it difficult to meet the multiple performance requirements of high-performance coatings.
A laser cladding technology assisted by a composite field of induction heating, ultrasonic oscillation and pulsed current is adopted. TC4 titanium alloy powder, IN718 high-temperature alloy powder and nitride ceramic powder are used. The temperature gradient is dynamically controlled by the induction heating field, the grains are refined by the ultrasonic oscillation field and the fluidity of the molten pool is improved by the pulsed current field, so as to form a high-density and high-strength multi-component composite coating.
It achieves high density, excellent bonding strength and hardness of high-entropy ceramic-reinforced coating, significantly improving the coating's wear resistance, corrosion resistance and high-temperature stability, making it suitable for equipment protection under extreme working conditions.
Smart Images

Figure CN120888926A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials surface engineering technology, specifically relating to a high-entropy ceramic reinforced coating based on induction heating, ultrasonic oscillation and pulsed current assisted laser cladding and its preparation method. Background Technology
[0002] Laser cladding technology is an advanced technique for surface modification and surface strengthening coating preparation. It uses a high-energy laser beam to melt strengthening powder and form a strengthening coating on the substrate surface. It is widely used in the preparation of high-performance coatings and parts repair in aerospace, energy equipment and other fields.
[0003] However, with the increasing demands on coating performance under extreme working conditions, traditional laser cladding technology has revealed the following key technical bottlenecks: the energy input mode of a single laser heat source leads to an extremely uneven temperature field distribution in the molten pool, which easily causes thermal stress concentration and induces microcrack networks; at the same time, the rapid cooling rate of laser cladding, coupled with insufficient gas escape from the molten pool and insufficient melt fluidity, leads to the appearance and growth of micropores in the coating, which seriously weakens the fatigue resistance and corrosion resistance of the coating; during the process of preparing reinforced coatings by laser cladding, the substrate-coating interface has unsatisfactory bonding strength due to the mismatch of thermal expansion coefficients, making it difficult to complete service operations under harsh conditions.
[0004] The multi-physics coupling mechanism of the molten pool flow field and temperature field is complex, and traditional laser cladding process parameter control struggles to address the following issues: Under the combined influence of surface tension and the Marangoni effect, the melt easily forms eddy current stagnation zones, exacerbating elemental segregation; insufficient molten pool cooling rate leads to continuous columnar crystal growth, and low-melting-point eutectic phases easily form at grain boundaries; second-phase ceramic particles float or sink due to density differences, resulting in gradient distribution failure and affecting the consistency of coating performance. Existing auxiliary field process optimization techniques have many shortcomings. While static preheating can effectively reduce thermal stress, it cannot dynamically match the molten pool thermal cycle, leading to excessive grain growth in the coating and affecting its mechanical properties; low-frequency ultrasonic-assisted cavitation effect is weak, resulting in limited grain refinement and severe energy attenuation, lacking energy efficiency and process feasibility.
[0005] Furthermore, existing traditional coating material systems are mostly limited to single alloy systems such as nickel-based and iron-based materials, which face inherent limitations in performance improvement: the solid solution strengthening limit of a single metal matrix is low, and even with the addition of hard phase particles for reinforcement, the coating hardness is still difficult to exceed 1000 HV, and it is also difficult to simultaneously meet the multiple performance requirements of high hardness, high-temperature oxidation resistance, and corrosion resistance. In recent years, although multi-component composite coatings such as high-entropy alloys have shown potential for performance breakthroughs, high-melting-point components such as TiN and NbN are difficult to completely melt under conventional laser power cladding, resulting in local enrichment of the reinforcing phase, which seriously affects the service performance of the coating.
[0006] In view of this, the present invention provides a high-entropy ceramic strengthening coating based on laser cladding assisted by induction heating, ultrasonic oscillation and pulsed current composite field and its preparation method. By dynamically controlling the composite field of induction heating, ultrasonic oscillation and pulsed current, the multi-field coupling synergistic strengthening effect is realized, breaking through the limitations of single material system and process, realizing the controllable preparation of high-density, high-strength, multi-component composite strengthening coating, and promoting cost reduction and efficiency improvement in the development and preparation of high-efficiency coatings. Summary of the Invention
[0007] One of the objectives of this invention is to provide a method for preparing a high-entropy ceramic reinforced coating based on induction heating, ultrasonic oscillation and pulsed current assisted laser cladding, so as to achieve the controllable preparation of a high-density, high-strength, multi-component composite reinforced coating.
[0008] The second objective of this invention is to provide a high-entropy ceramic reinforcement coating with excellent performance, good formability, and high-quality bonding with the substrate.
[0009] The third objective of this invention is to provide an application of a high-entropy ceramic reinforced coating with excellent hardness, wear resistance, corrosion resistance, and high-temperature resistance in the protection of equipment substrate surfaces.
[0010] One of the technical solutions adopted to achieve the objective of this invention is to provide a method for preparing a high-entropy ceramic reinforced coating based on induction heating, ultrasonic oscillation and pulsed current assisted laser cladding. The method uses a composite powder composed of TC4 titanium alloy powder, IN718 high-temperature alloy powder and nitride ceramic powder as raw materials, and uses laser cladding to process and prepare a reinforced coating on the surface of a substrate. The laser cladding is carried out under the combined assisted conditions of an induction heating field, an ultrasonic oscillation field and a pulsed current field.
[0011] The overall concept of this invention is as follows: To achieve the preparation of high-performance multi-component composite coatings, the composite powder used in the laser cladding of this invention consists of TC4 titanium alloy powder, IN718 high-temperature alloy powder, and nitride ceramic powder. TC4 titanium alloy enhances the coating's specific strength and fatigue resistance, strengthens its electrochemical corrosion resistance, and its low density effectively reduces the overall density of the composite coating. IN718 high-temperature alloy imparts high-temperature stability and oxidation corrosion resistance to the coating through γ'' phase strengthening and solid solution strengthening. The synergistic effect of the dual-phase metal matrix in the coating achieves simultaneous enhancement of the coating's mechanical properties and corrosion resistance. Simultaneously, using nitride ceramic as a powder as a hard reinforcing phase significantly improves the hardness, wear resistance, and high-temperature stability of the cladding layer, while refining the grain size and improving corrosion resistance.
[0012] Furthermore, considering the cladding characteristics of TC4 titanium alloy powder and IN718 high-temperature alloy powder, as well as the strengthening mechanism of nitride ceramic powder, the laser cladding of this invention is carried out under the combined assistance of an induction heating field, an ultrasonic oscillation field, and a pulsed current field. Specifically, the induction heating field dynamically matches the heat input of the laser cladding, achieving real-time optimization of the molten pool temperature field and effectively reducing residual stress; the ultrasonic oscillation field suppresses ceramic phase segregation and agglomeration, controlling the refinement of the average grain size of the coating; the pulsed current of the pulsed current field applies an electromigration driving force to the atoms, forming high-intensity eddies within the molten pool, improving the fluidity of the molten pool, avoiding the generation of pores in the coating, and simultaneously forcibly diffusing nano-ceramic particles, resulting in near-segregation-free solidification during the dynamic process of molten pool solidification, further improving the coating quality.
[0013] Furthermore, the nitride ceramic powder is composed of titanium nitride, niobium nitride, chromium nitride, aluminum nitride, and vanadium nitride. Among them, TiN combines high hardness and low coefficient of thermal expansion, effectively suppressing grain boundary migration through the pinning effect and refining the coating grains to the submicron level; NbN has excellent high-temperature oxidation resistance and high-temperature wear resistance, and can form a coherent interface with the metal matrix in the coating, effectively refining the grain size and contributing to the mechanical properties of the coating; CrN has excellent corrosion resistance and high-temperature stability, which can significantly improve the corrosion resistance of the cladding layer in harsh environments such as acid and salt spray, and can still maintain high hardness at high temperatures, effectively resisting wear under high-temperature conditions; AlN has high thermal conductivity and low coefficient of thermal expansion, which can optimize the high-temperature stability of the cladding layer, reduce thermal stress accumulation, and suppress crack formation; the high-temperature stability of AlN can enhance the thermal shock resistance of the coating, making it suitable for high-temperature cyclic conditions; VN improves the hardness of the coating while also having a certain degree of toughness, and its unique dislocation pinning effect can effectively hinder plastic deformation and enhance the fatigue resistance of the coating; in addition, VN forms a dense oxide layer at high temperatures, further slowing down the high-temperature oxidation rate of the coating, making it particularly suitable for extreme environments with high loads and complex stresses. With the combined assistance of induction heating, ultrasonic oscillation and pulsed current, the above five nitride ceramic powders are laser cladized to form (TiNbCrAlV)N high-entropy ceramics, which strengthen the composite coating.
[0014] Further, the composite powder, by weight percentage, comprises: 30%-40% TC4 titanium alloy powder, 21%-42% IN718 high-temperature alloy powder, 6%-8% titanium nitride, 3%-5% niobium nitride, 5%-7% chromium nitride, 9%-12% aluminum nitride, and 5%-7% vanadium nitride; the particle size of the TC4 titanium alloy powder and IN718 high-temperature alloy powder is 80-100 μm; the particle size of the nitride ceramic powder is 120-200 nm. In this invention, by optimizing the content of nitride ceramic powder in the composite powder, both strength and toughness and interfacial bonding can be balanced, avoiding brittle cracking. The nitride ceramic powder, with a particle size of 120-200 nm, possesses nanoscale characteristics, and can be more uniformly dispersed in the TC4 / IN718 coating matrix during laser cladding, significantly refining the grains and enhancing interfacial bonding, while simultaneously improving the mechanical properties of the coating through dispersion strengthening.
[0015] Furthermore, in the laser cladding process, the laser power is 2000-2800W, the scanning speed is 16-22mm / s, the powder feeding rate is 40-60 g / min, the overlap rate is 20%-40%, and the laser focal length is 16-20mm. An inert gas is used to protect the laser cladding process, with a flow rate of 400-600L / h. Preferably, the inert gas is argon.
[0016] Furthermore, the heating coils of the induction heating field are arranged around the substrate; the duration of the induction heating field includes preheating before laser cladding, assistance during laser cladding, and cooling stage after laser cladding; the frequency of the induction heating field is 50-200kHz, the heating temperature is 600-900℃; the preheating time is 120-240s; and the cooling rate during the cooling stage is 50-100℃ / min.
[0017] The induction heating field of this invention encompasses the substrate at its center and acts on the entire substrate. The induction heating field and laser cladding adopt a vertical spatial configuration, making the perpendicular bisector of the induction heating field parallel to the laser beam, thus achieving spatial coupling between the thermal field and the laser. This helps to achieve uniform control of the molten pool temperature gradient and avoids temperature field unevenness caused by heat input separation and loss.
[0018] Furthermore, the technical characteristics of laser cladding are high heat input and rapid cooling. This invention matches the high-frequency induction heating field with the heat input of laser cladding. Before laser cladding, the substrate is preheated at a temperature of 600-900℃ to match the various high-melting-point nitride ceramic components in the composite powder. This reduces the temperature difference between the substrate and the molten pool during cladding, promotes the melting of the ceramic phase, and improves the fluidity of the molten pool. Simultaneously, after laser cladding, the induction heating field is used to perform programmed cooling at a rate of 50-100℃ / min to precisely control the grain growth process. Induction heating slows down the cooling rate after cladding, avoids thermal stress concentration, and improves the quality of the prepared coating.
[0019] Furthermore, the ultrasonic oscillation generator of the ultrasonic oscillation field is coaxially nested outside the laser head of the laser cladding, located above the substrate along with the laser head. The vertical distance between the ultrasonic transducer of the ultrasonic oscillation field and the substrate surface is 2-5 mm. In the ultrasonic oscillation field, the oscillation frequency is 20-45 kHz, the amplitude is 10-50 μm, and the duty cycle is 20%-40%. The ultrasonic oscillation field used in this invention avoids energy overload by controlling the distance between the ultrasonic transducer and the substrate surface and the pulse duty cycle. Addressing the tendency of nano-ceramics to agglomerate, it suppresses nitride ceramic segregation through cavitation. This pulsed ultrasonic synchronous laser cladding, using a relatively high amplitude of 10-50 μm, enhances the molten pool flow field disturbance, strengthens the stirring intensity of the high-viscosity molten pool containing nano-ceramics, optimizes the dispersion of nano-ceramic particles, and solves the problems of molten pool splashing and coating micropores caused by continuous ultrasonic fields.
[0020] Furthermore, the pulsed current generator of the pulsed current field is connected to the substrate to be clad via wires; in the pulsed current field, the pulse width is 20-60 μs; the current amplitude is 600-1000 A; the frequency is 20-40 kHz; and the duty cycle is 20%-40%. During the assisted process of the pulsed current field, the pulsed current exerts an electromigration driving force on the atoms, forming high-intensity eddies within the molten pool, improving the fluidity of the molten pool, avoiding the generation of pores in the coating, and simultaneously forcing the diffusion of nano-ceramic particles, resulting in almost no segregation during the dynamic process of molten pool solidification. Traditional continuous current leads to continuous overheating and a strong tendency for grain coarsening, while pulsed current can apply periodic Joule heating, which, in synergy with the ultrasonic field, further suppresses the agglomeration and segregation of nano-scale ceramic phases during laser cladding, thereby significantly refining the coating grains and improving the coating density.
[0021] Furthermore, the method for preparing a high-entropy ceramic reinforced coating based on induction heating, ultrasonic oscillation, and pulsed current-assisted laser cladding provided by the present invention includes the following steps: S1. Mix TC4 titanium alloy powder, IN718 high-temperature alloy powder and nitride ceramic powder, and obtain composite powder after pretreatment. S2. Set the operating parameters for laser cladding, induction heating field, ultrasonic oscillation field, and pulsed current field; S3. Start the induction heating field to preheat the substrate; after preheating, simultaneously start the ultrasonic oscillation field, pulsed current field and laser cladding equipment, and perform laser cladding on the preheated substrate with the combined assistance of the induction heating field, ultrasonic oscillation field and pulsed current field; S4. After the laser cladding is completed, turn off the laser cladding equipment, ultrasonic oscillation field and pulsed current field, and use the induction heating field to control the cooling rate until room temperature.
[0022] Further, in step S1, the method for preparing the composite powder includes the following steps: selecting TC4 titanium alloy powder, IN718 high-temperature alloy powder, and nitride ceramic powder according to a mass ratio, mixing them thoroughly, and then subjecting them to ball milling and vacuum drying to obtain the composite powder. Preferably, the ball milling speed is 180-300 rpm, the ball milling time is 1-3 hours, and the ball-to-material ratio is 6-9:1; the vacuum drying temperature is 50-75℃, and the drying time is 5-8 hours.
[0023] Furthermore, prior to step S2, the substrate is pretreated, including the following steps: grinding the substrate with an angle grinder to remove oxide scale, sandblasting the substrate, cleaning the substrate with acetone, and finally drying.
[0024] The second objective of this invention is achieved by providing a high-entropy ceramic strengthening coating based on induction heating, ultrasonic oscillation, and pulsed current-assisted laser cladding, which is prepared by the preparation method described in one of the objectives of this invention.
[0025] The third objective of this invention is to provide an application of the high-entropy ceramic strengthening coating described in the second objective of this invention in the surface protection of gas turbine blades.
[0026] The high-entropy ceramic reinforced coating prepared by this invention has advantages such as high temperature resistance, corrosion resistance, thermal shock resistance, and good high-temperature service stability. It is highly matched with the performance requirements of gas turbine blades under extreme conditions such as high temperature and high stress. Applying it to the surface protection of gas turbine blades can significantly improve the high-temperature mechanical properties, oxidation resistance, and service life of the blades.
[0027] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention provides a method for preparing a high-entropy ceramic reinforced coating based on induction heating, ultrasonic oscillation, and pulsed current-assisted laser cladding. The raw material powder for laser cladding is a bimetallic matrix composed of TC4 titanium alloy powder and IN718 high-temperature alloy powder, and is formulated with various nitride ceramic reinforcing phases. The high-performance coating is prepared by using a combination of induction heating field, ultrasonic oscillation field, and pulsed electromagnetic field to assist laser cladding. Among them, the induction heating field dynamically controls the temperature gradient, the ultrasonic oscillation field refines the grains through cavitation effect, and the pulsed electromagnetic field applies periodic Joule heating. These effects work synergistically with the ultrasonic oscillation field to further suppress the agglomeration and segregation of nanoscale ceramic phases during laser cladding, thereby significantly refining the coating grains and improving the coating density. The high-energy and precise energy input of laser cladding and the dynamic synergistic coupling of multiple fields enable real-time optimization of the molten pool temperature, reduce residual stress, significantly reduce coating porosity, and improve the bonding strength of the coating-substrate interface. The preparation method provided by this invention is simple, has high production efficiency, and low cost for mass production, providing an efficient and low-cost solution for the industrial application of high-performance coatings.
[0028] (2) The high-entropy ceramic-reinforced coating prepared by this invention exhibits excellent comprehensive performance. Based on the preparation process of multi-field assisted laser cladding, the coating porosity is controlled to be ≤0.05%, the bonding strength between the coating and the substrate is ≥520MPa, the residual stress is reduced by more than 40%, and the average grain size in the coating is not higher than 20μm. In addition, the coating uses a bimetallic matrix composed of TC4 titanium alloy powder and IN718 high-temperature alloy powder combined with a high-entropy ceramic reinforcing phase. The coating has high hardness and excellent wear resistance, oxidation resistance, salt spray corrosion resistance and electrochemical corrosion resistance. It has broad application prospects in the surface protection of mechanical equipment, such as gas turbine blades. Attached Figure Description
[0029] Figure 1 This is a schematic diagram illustrating the preparation of a high-entropy ceramic reinforced coating using a laser cladding process assisted by a composite field of induction heating and ultrasonic oscillation, as described in an embodiment of the present invention. Figure 2 This is a scanning electron microscope image of the bonding region between the high-entropy ceramic reinforced coating and the Q235 substrate obtained in Example 1 of the present invention; Figure 3 This is a scanning electron microscope image of the top region of the high-entropy ceramic reinforced coating obtained in Example 1 of the present invention; Among them, 1-multi-component reinforced coating, 2-fusion interface, 3-Q235 substrate. Detailed Implementation
[0030] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other.
[0032] This invention provides a method for preparing a high-entropy ceramic reinforced coating based on induction heating, ultrasonic oscillation, and pulsed current-assisted laser cladding, as illustrated in the schematic diagram. Figure 1 As shown, the preparation method includes the following steps: Step 1: Mix TC4 titanium alloy powder, IN718 high-temperature alloy powder, and nitride ceramic powder, and pre-treat to obtain composite powder. The composition of the composite powder, by weight percentage, includes: 30%-40% TC4 titanium alloy powder, 21%-42% IN718 high-temperature alloy powder, 6%-8% titanium nitride, 3%-5% niobium nitride, 5%-7% chromium nitride, 9%-12% aluminum nitride, and 5%-7% vanadium nitride. The particle size of TC4 titanium alloy powder and IN718 high-temperature alloy powder is 80-100 μm; the particle size of nitride ceramic powder is 120-200 nm. The preparation method of the composite powder is as follows: Select TC4 titanium alloy powder, IN718 high-temperature alloy powder, and nitride ceramic powder according to the mass ratio, mix them thoroughly, and then ball mill and vacuum dry to obtain composite powder. The ball milling process involves a rotation speed of 180-300 rpm, a milling time of 1-3 hours, and a ball-to-material ratio of 6-9:1. The vacuum drying process involves a temperature of 50-75℃ and a drying time of 5-8 hours.
[0033] Step 2: Pre-treat the substrate, including the following steps: grind the substrate with an angle grinder to remove oxide scale, sandblast the substrate, clean the substrate with acetone, and finally dry it; set the working parameters of laser cladding, induction heating field, ultrasonic oscillation field and pulsed current field; In the laser cladding process, the laser power is 2000-2800W, the scanning speed is 16-22mm / s, the powder feeding rate is 40-60g / min, the overlap rate is 20%-40%, and the laser focal length is 16-20mm. Inert gas is used to protect the laser cladding process, and the inert gas flow rate is 400-600L / h. The heating coils of the induction heating field are arranged around the substrate; the duration of the induction heating field includes preheating before laser cladding, assistance during laser cladding, and cooling after laser cladding; the frequency of the induction heating field is 50-200kHz, and the heating temperature is 600-900℃. The ultrasonic oscillation generator of the ultrasonic oscillation field is coaxially nested and set outside the laser head of the laser cladding. The vertical distance between the ultrasonic transducer and the substrate surface is 2-5 mm. In the ultrasonic oscillation field, the oscillation frequency is 20-45 kHz, the amplitude is 10-50 μm, and the duty cycle is 20%-40%. The pulse current generator of the pulse current field is connected to the substrate to be clad via an electric wire; in the pulse current field, the pulse width is 20-60μs; the current amplitude is 600-1000A; the frequency is 20-40kHz; and the duty cycle is 20%-40%.
[0034] Step 3: Start the induction heating field to preheat the substrate for 120-240 seconds; after preheating, simultaneously start the ultrasonic oscillation field, pulsed current field and laser cladding equipment, and perform laser cladding on the preheated substrate with the combined assistance of the induction heating field, ultrasonic oscillation field and pulsed current field. Step 4: After the laser cladding is completed, turn off the laser cladding equipment, ultrasonic oscillation field and pulsed current field, and use the induction heating field to control the cooling rate at 50-100℃ / min until room temperature.
[0035] The present invention will be further described below with reference to specific embodiments, but these are not intended to limit the scope of the invention.
[0036] The composition (parts by weight) of the composite powder used in laser cladding in Examples 1-3 is shown in Table 1 below.
[0037] Table 1
[0038] In the table above, the particle size of TC4 titanium alloy powder and IN718 high-temperature alloy powder is 80-100μm; the particle size of nitride ceramic powder is 120-200nm.
[0039] Example 1 This embodiment provides a method for preparing a high-entropy ceramic reinforced coating based on induction heating, ultrasonic oscillation, and pulsed current-assisted laser cladding, including the following steps: Step 1: Prepare the raw material powders according to the following mass percentages: 35 wt.% TC4 titanium alloy, 30 wt.% IN718 high-temperature alloy, 7.2 wt.% TiN ceramic powder, 4 wt.% NbN ceramic powder, 6.7 wt.% CrN ceramic powder, 10.2 wt.% AlN ceramic powder, and 6.9 wt.% VN ceramic powder; wherein the average particle size of the alloy powder is 90 μm and the average particle size of the ceramic powder is 160 nm. The aforementioned raw material powder was ball-milled to ensure uniform mixing. The ball-milling parameters were selected as follows: ball milling speed 240 rpm, ball milling time 2 h, and ball-to-material ratio 7:1. Then, the ball-milled raw material powder was vacuum-dried. The vacuum drying parameters were selected as follows: drying temperature 60℃, and drying time 6.5 h. After vacuum drying, high-efficiency multi-component raw material powder was obtained. Step 2: Grind the Q235 substrate with an angle grinder to remove oxide scale; sandblast the ground Q235 substrate; clean the sandblasted Q235 substrate with acetone; finally, dry it; set the parameters of the induction heating device, ultrasonic oscillation device, pulse current generator, and laser cladding in sequence: Induction heating field parameters: frequency 125kHz, heating temperature 750℃; preheating time 180s; cooling rate after cladding 75℃ / min; Ultrasonic oscillation field parameters: frequency 30kHz, amplitude 30μm, duty cycle 30%, vertical distance between the ultrasonic transducer and the Q235 substrate surface 3.5mm; Pulse current field parameters: pulse width 40μs, current amplitude 800A, frequency 30kHz, duty cycle 30%; set the laser cladding parameters, including laser cladding power 2400W, scanning speed 19mm / s; powder feed rate 50%. g / min; overlap rate 30%; laser focal length 18mm; inert protective gas flow rate 500L / h; Step 3: Place the treated Q235 substrate on the processing platform, then load the treated powder into the laser cladding system and introduce protective gas; then input the set induction heating, ultrasonic oscillation, and laser cladding parameters into the system; start the induction heating field to preheat the substrate for 180 seconds; after preheating, simultaneously start the ultrasonic oscillation field, pulsed current field, and laser cladding equipment. Under the combined assistance of the induction heating field, ultrasonic oscillation field, and pulsed current field, laser cladding is performed on the preheated substrate to obtain a high-entropy ceramic reinforced coating; Step 4: After the laser cladding is completed, turn off the laser cladding equipment, ultrasonic oscillation field and pulsed current field, and use the induction heating field to control the cooling rate at 75℃ / min until room temperature.
[0040] Scanning electron microscopy (SEM) was used to characterize and analyze the bonding region between the high-entropy ceramic reinforced coating prepared by multi-field coupling and the Q235 substrate, as well as the typical morphology of the coating region. Figure 2 As shown in the figure, analysis of the SEM images yields the following conclusions: the fusion line between the high-entropy ceramic-reinforced coating and the Q235 substrate is smooth and natural, with no interfacial fractures or sharp fluctuations observed, indicating an excellent metallurgical bond between the coating and the Q235 substrate; the high-entropy ceramic-reinforced coating region exhibits a high-quality microstructure morphology, with no observed agglomeration or precipitation of ceramic phases, and the average grain size in the coating region is approximately 5.95 micrometers, indicating excellent microstructural characteristics; the coating region shows no defects such as cracks, pores, or inclusions, indicating excellent forming quality.
[0041] Figure 3 The scanning electron microscope (SEM) images shown indicate that the top region of the high-entropy ceramic-reinforced coating prepared by multi-field coupling exhibits a fine, uniform, and dense equiaxed crystal structure with an average grain size of approximately 3.57 μm. Simultaneously, it was observed that the high-entropy ceramics formed during the preparation process are dispersed at the equiaxed grain boundaries in submicron sizes. These dispersed high-entropy ceramics act as pinning agents, effectively suppressing grain coarsening and thus enhancing the coating's service performance and lifespan under high-temperature conditions. Furthermore, the high-entropy ceramics, through solid solution strengthening and grain refinement mechanisms, synergistically improve the coating's hardness and toughness, significantly suppressing the initiation and propagation of thermal shock cracks, thereby enhancing its service thermal stability.
[0042] Example 2 This embodiment provides a method for preparing a high-entropy ceramic reinforced coating based on induction heating, ultrasonic oscillation, and pulsed current-assisted laser cladding, including the following steps: Step 1: Prepare the raw material powders according to the following mass percentages: 30 wt.% TC4 titanium alloy, 42 wt.% IN718 high-temperature alloy, 6 wt.% TiN ceramic powder, 3 wt.% NbN ceramic powder, 5 wt.% CrN ceramic powder, 9 wt.% AlN ceramic powder, and 5 wt.% VN ceramic powder; wherein the average particle size of the alloy powder is 80 μm and the average particle size of the ceramic powder is 180 nm. The aforementioned raw material powder was ball-milled to ensure uniform mixing. The ball-milling parameters were selected as follows: ball milling speed 200 rpm, ball milling time 3 h, and ball-to-material ratio 8:1. The ball-milled raw material powder was then subjected to vacuum drying. The vacuum drying parameters were selected as follows: drying temperature 65℃, and drying time 7 h. After vacuum drying, high-efficiency multi-component raw material powder was obtained. Step 2: Grind the Q235 substrate with an angle grinder to remove oxide scale; sandblast the ground Q235 substrate; clean the sandblasted Q235 substrate with acetone; finally, dry it; set the parameters of the induction heating device, ultrasonic oscillation device, pulse current generator, and laser cladding in sequence: Induction heating field parameters: frequency 200kHz, heating temperature 900℃; preheating time 240s; cooling rate after cladding 100℃ / min; Ultrasonic oscillation field parameters: frequency 20kHz, amplitude 10μm, duty cycle 20%, vertical distance between the ultrasonic transducer and the Q235 substrate surface 2mm; Pulse current field parameters: pulse width 20μs, current amplitude 600A, frequency 20kHz, duty cycle 20%; set the laser cladding parameters, including setting the laser cladding power to 2000W, scanning speed to 16mm / s; powder feed rate to 40%. g / min; overlap rate 40%; laser focal length 16mm; inert protective gas flow rate 400L / h; Step 3: Place the treated Q235 substrate on the processing platform; then load the treated powder into the laser cladding system and introduce protective gas; then input the set induction heating, ultrasonic oscillation, and laser cladding parameters into the system; start the induction heating field to preheat the substrate for 240 seconds; after preheating, simultaneously start the ultrasonic oscillation field, pulsed current field, and laser cladding equipment. Under the combined assistance of the induction heating field, ultrasonic oscillation field, and pulsed current field, laser cladding is performed on the preheated substrate to obtain a high-entropy ceramic reinforced coating; Step 4: After the laser cladding is completed, turn off the laser cladding equipment, ultrasonic oscillation field and pulsed current field, and use the induction heating field to control the cooling rate at 100℃ / min until room temperature.
[0043] Example 3 This embodiment provides a method for preparing a high-entropy ceramic reinforced coating based on induction heating, ultrasonic oscillation, and pulsed current-assisted laser cladding, including the following steps: Step 1: Prepare the raw material powders according to the following mass percentages: 40 wt.% TC4 titanium alloy, 21 wt.% IN718 high-temperature alloy, 8 wt.% TiN ceramic powder, 5 wt.% NbN ceramic powder, 7 wt.% CrN ceramic powder, 12 wt.% AlN ceramic powder, and 7 wt.% VN ceramic powder; wherein the average particle size of the alloy powder is 90 μm and the average particle size of the ceramic powder is 160 nm. The aforementioned raw material powder was ball-milled to ensure uniform mixing. The ball milling parameters were selected as follows: ball milling speed 280 rpm, ball milling time 1.5 h, and ball-to-material ratio 8:1. Then, the ball-milled raw material powder was vacuum-dried. The vacuum drying parameters were selected as follows: drying temperature 55℃, drying time 5 h. After vacuum drying, high-efficiency multi-component raw material powder was obtained. Step 2: Grind the Q235 substrate with an angle grinder to remove oxide scale; sandblast the ground Q235 substrate; clean the sandblasted Q235 substrate with acetone; finally, dry it; set the parameters of the induction heating device, ultrasonic oscillation device, pulse current generator, and laser cladding in sequence: Induction heating field parameters: frequency 50kHz, heating temperature 600℃; preheating time 120s; cooling rate after cladding 50℃ / min; Ultrasonic oscillation field parameters: frequency 45kHz, amplitude 50μm, duty cycle 40%, vertical distance between the ultrasonic transducer and the Q235 substrate surface 5mm; Pulse current field parameters: pulse width 60μs, current amplitude 1000A, frequency 40kHz, duty cycle 40%; set the laser cladding parameters, including laser cladding power 2800W, scanning speed 22mm / s; powder feed rate 60%. g / min; overlap rate 20%, laser focal length 20mm; inert protective gas flow rate 600L / h; Step 3: Place the treated Q235 substrate on the processing platform; then load the treated powder into the laser cladding system and introduce protective gas; then input the set induction heating, ultrasonic oscillation, and laser cladding parameters into the system; start the induction heating field to preheat the substrate for 120 seconds; after preheating, simultaneously start the ultrasonic oscillation field, pulsed current field, and laser cladding equipment. Under the combined assistance of the induction heating field, ultrasonic oscillation field, and pulsed current field, laser cladding is performed on the preheated substrate to obtain a high-entropy ceramic reinforced coating; Step 4: After the laser cladding is completed, turn off the laser cladding equipment, ultrasonic oscillation field and pulsed current field, and use the induction heating field to control the cooling rate at 50℃ / min until room temperature.
[0044] Performance testing The high-entropy ceramic reinforced coatings prepared in Examples 1-3 were subjected to performance tests, including coating porosity, bonding strength, residual stress, and average grain size. The test methods for each performance parameter are as follows: (1) Porosity: After high-precision polishing, the metallographic microscope was used for characterization and observation, and the porosity was calculated using image processing software and data statistics software.
[0045] (2) Bond strength: The bond strength test was conducted at room temperature using a universal testing machine (WGW-100H, Kexin, Changchun, China) with the aid of a tensile testing fixture assembly. The maximum load capacity was ±100 kN, and the displacement rate was 1 mm / min. During the experiment, the load and displacement were recorded by a computer data acquisition system.
[0046] (3) Residual stress: X-ray diffraction method, measuring the lattice strain (diffraction peak shift) of the coating, and calculating the stress through elastic strain.
[0047] (4) Average grain size of coating: After polishing, the cross section of the coating was etched and observed using SEM. The number and size of grains were counted using image processing software and data statistics software, and then the average grain size was calculated.
[0048] The relevant performance test data of the high-entropy ceramic reinforced coatings prepared in Examples 1-3 are shown in Table 2 below.
[0049] Table 2
[0050] As can be seen from the above table, The high-entropy ceramic reinforced coatings prepared in Examples 1-3 of this invention have a coating porosity of ≤0.05%, a coating-substrate bonding strength of ≥520MPa, a residual stress reduction of more than 40%, and an average grain size within the coating of no more than 20μm.
[0051] Furthermore, the bimetallic matrix composed of TC4 titanium alloy powder and IN718 high-temperature alloy powder, combined with the high-entropy ceramic reinforcing phase, gives the coating excellent application performance, with a microhardness of not less than 2800 HV and a wear rate of not more than 2.8 × 10⁻⁶. -6 mm 3 N -1 m -1 Oxidation weight gain at 1000℃ / 100h <1.2mg / cm³ 2 The hardness retention rate at 1000℃ is over 95%, with no performance degradation due to phase transformation. No pitting corrosion occurred after 2400 hours of salt spray testing, and the electrochemical corrosion current density of the coating is no higher than 1.88 × 10⁻⁶. -8 A / cm 2 It has broad application prospects in the surface protection of mechanical equipment, such as gas turbine blades.
[0052] The above are merely preferred embodiments of the present invention and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should recognize that any equivalent substitutions and obvious changes made based on the content of this specification should be included within the protection scope of the present invention.
Claims
1. A method for preparing a high-entropy ceramic reinforced coating based on induction heating, ultrasonic oscillation, and pulsed current-assisted laser cladding, characterized in that, A reinforced coating is prepared on the substrate surface by laser cladding using a composite powder composed of TC4 titanium alloy powder, IN718 high-temperature alloy powder and nitride ceramic powder as raw materials; the laser cladding is carried out under the combined auxiliary conditions of an induction heating field, an ultrasonic oscillation field and a pulsed current field.
2. The preparation method according to claim 1, characterized in that, The nitride ceramic powder is composed of titanium nitride, niobium nitride, chromium nitride, aluminum nitride, and vanadium nitride.
3. The preparation method according to claim 2, characterized in that, The composite powder comprises, by weight percentage: 30%-40% TC4 titanium alloy powder, 21%-42% IN718 high-temperature alloy powder, 6%-8% titanium nitride, 3%-5% niobium nitride, 5%-7% chromium nitride, 9%-12% aluminum nitride, and 5%-7% vanadium nitride; the particle size of the TC4 titanium alloy powder and the IN718 high-temperature alloy powder is 80-100 μm; and the particle size of the nitride ceramic powder is 120-200 nm.
4. The preparation method according to claim 1, characterized in that, In the laser cladding process, the laser power is 2000-2800W, the scanning speed is 16-22mm / s, the powder feeding rate is 40-60g / min, the overlap rate is 20%-40%, and the laser focal length is 16-20mm. An inert gas is used to protect the laser cladding process, and the inert gas flow rate is 400-600L / h.
5. The preparation method according to claim 1, characterized in that, The heating coils of the induction heating field are arranged around the substrate; the duration of the induction heating field includes preheating before laser cladding, assistance during laser cladding, and cooling after laser cladding; the frequency of the induction heating field is 50-200kHz, the heating temperature is 600-900℃, the preheating time is 120-240s, and the cooling rate during the cooling stage is 50-100℃ / min.
6. The preparation method according to claim 1, characterized in that, The ultrasonic oscillation generator of the ultrasonic oscillation field is set outside the laser head of the laser cladding in a coaxial nesting manner. The vertical distance between the ultrasonic transducer and the substrate surface is 2-5 mm. In the ultrasonic oscillation field, the oscillation frequency is 20-45 kHz, the amplitude is 10-50 μm, and the duty cycle is 20%-40%.
7. The preparation method according to claim 1, characterized in that, The pulse current generator of the pulse current field is connected to the substrate to be clad via an electric wire; in the pulse current field, the pulse width is 20-60μs; the current amplitude is 600-1000A; the frequency is 20-40kHz; and the duty cycle is 20%-40%.
8. The preparation method according to claim 1, characterized in that, Includes the following steps: S1. Mix TC4 titanium alloy powder, IN718 high-temperature alloy powder and nitride ceramic powder, and obtain composite powder after pretreatment. S2. Set the operating parameters for laser cladding, induction heating field, ultrasonic oscillation field, and pulsed current field; S3. Start the induction heating field to preheat the substrate; after preheating, simultaneously start the ultrasonic oscillation field, pulsed current field and laser cladding equipment, and perform laser cladding on the preheated substrate with the combined assistance of the induction heating field, ultrasonic oscillation field and pulsed current field; S4. After the laser cladding is completed, turn off the laser cladding equipment, ultrasonic oscillation field and pulsed current field, and use the induction heating field to control the cooling rate until room temperature.
9. A high-entropy ceramic strengthening coating based on induction heating, ultrasonic oscillation, and pulsed current-assisted laser cladding, characterized in that, It is prepared by the method according to any one of claims 1-8.
10. The application of the high-entropy ceramic reinforced coating according to claim 9 in the surface protection of gas turbine blades.
Citation Information
Cited By
Crack-free high-density high-toughness Ni3Al-based alloy component formed by acoustic resonance assisted LED (Light Emitting Diode) and preparation method of crack-free high-density high-toughness Ni3Al-based alloy component
CN121624453A